The induction of ethylene response factor 3 (ERF3) in potato as a result of co-inoculation with pseudomonas sp. r41805 and rhizophagus irregularis MUCL 41833 a possible role in plant defense - Velivelli, S. (2017)
Colonization of plant rhizosphere/roots by beneficial microorganisms (e.g. plant growth promoting rhizobacteria PGPR, arbuscular mycorrhizal fungi AMF) confers broad-spectrum resistance to virulent pathogens and is known as induced systemic resistance (ISR) and mycorrhizal-induced resistance (MIR). ISR or MIR, an indirect mechanism for biocontrol, involves complex signaling networks that are regulated by several plant hormones, the most important of which are salicylic acid (SA), jasmonic acid (JA) and ethylene (ET). In the present study, we investigated if inoculation of potato plantlets with an AMF (Rhizophagus irregularis MUCL 41833) and a PGPR (Pseudomonas sp R41805) either alone or in combination, could elicit host defense response genes in the presence or absence of Rhizoctonia Solani EC-1, a major potato pathogen. RT-qPCR revealed the significant expression of ethylene response factor 3 (EFR3) in mycorrhized potato plantlets inoculated with Pseudomonas sp R41805 and also in mycorrhized potato plantlets inoculated with Pseudomonas sp R41805 and challenged with R. solani. The significance of ethylene response factors (ERFs) in pathogen defense has been well documented in the literature. The results of the present study suggest that the dual inoculation of potato with PGPR and AMF may play a part in the activation of plant systemic defense systems via ERF3. © 2015 Taylor & Francis Group, LLC.